2010
DOI: 10.1086/647940
|View full text |Cite
|
Sign up to set email alerts
|

Lessons Learned from the Anaerobe Survey: Historical Perspective and Review of the Most Recent Data (2005–2007)

Abstract: In summary, resistance to antibiotics was greater among non-B. fragilis Bacteroides species than among B. fragilis and was especially greater among species with a low frequency of isolation, such as Bacteroides caccae and B. uniformis. The emergence of resistance among the non-B. fragilis Bacteroides species underscores the need for speciation of B. fragilis group isolates and for clinicians to be aware of associations between species and drug resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
93
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(98 citation statements)
references
References 20 publications
5
93
0
Order By: Relevance
“…Resistance to even the most active drugs, such as imipenem, piperacillin-tazobactam, ampicillin-sulbactam, and metronidazole, has been reported (23,25,26). Furthermore, there are clear differences in the geographic patterns of resistance and even differences in resistance patterns in different hospitals in a single city, perhaps due in part to the variability in prescribing patterns (27). Numbers of reports of broadly multidrug-resistant B. fragilis strains as well as numbers of reports of resistance arising during treatment have increased (6,11,14,22,28).…”
Section: Susceptibilty Testing Of Anaerobic Bacteriamentioning
confidence: 99%
See 2 more Smart Citations
“…Resistance to even the most active drugs, such as imipenem, piperacillin-tazobactam, ampicillin-sulbactam, and metronidazole, has been reported (23,25,26). Furthermore, there are clear differences in the geographic patterns of resistance and even differences in resistance patterns in different hospitals in a single city, perhaps due in part to the variability in prescribing patterns (27). Numbers of reports of broadly multidrug-resistant B. fragilis strains as well as numbers of reports of resistance arising during treatment have increased (6,11,14,22,28).…”
Section: Susceptibilty Testing Of Anaerobic Bacteriamentioning
confidence: 99%
“…Surveillance tests have been conducted for years by groups worldwide and reflect sweeping general trends (18,24,27,33,34,147) However, these results will not necessarily reflect the patterns of specific patients or hospitals. Because of this, the CLSI strongly recommends that hospitals conduct at least annual surveillance antimicrobial susceptibility testing to elucidate their local patterns.…”
Section: Surveillance Tests For Particular Hospitals or Geographic Rementioning
confidence: 99%
See 1 more Smart Citation
“…In the latter species, metronidazole and carbapenem resistance have recently been described (22). Since the growth of B. vulgatus on BFS agar is inhibited (Table 1), the medium is not suitable for recovery of this antibiotic-resistant species (23). In the validation with clinical specimens, 59 of the 1,209 specimens had growth of Enterobacteriaceae, but their colony morphologies were different from the morphology of B. fragilis.…”
Section: Resultsmentioning
confidence: 99%
“…It has been observed that resistance to beta-lactams in obligate and facultative anaerobic organisms is maily associated with Extended Spectrum Beta Lactamase (ESBL) and Metallo Beta Lactamse (MBL) production (Snydman et al, 2010). Whereas mechanism for metronidazole resistance in B. fragilis include the presence of nim genes, which encode 5-nitroimidazole reductases that convert metronidazole to a non-toxic amino derivative (Pumbwe et al, 2008), overexpression of the DNA repair protein, RecA (Steffens et al, 2010) and disruption of the electron transport chain (Lynch et al, 2013).…”
Section: But Comprising Least Common Bacteroides Occur Inmentioning
confidence: 99%